AN ANALYSIS ON ESP TO STUDENTS OF READING MATERIAL - Ningrum, Sulis Tia (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2015)
Material in teaching ESP is very important. This paper is to analyze students’ reading material on ESP. Governmental science department is chosen because of this department applies reading and it focuses on reading comprehension. English as a Foreign Language (EFL) is divided into General English (GE) and English for Specific Purposes (ESP). English is learnt because of the students’ purposes. In this article, reading material is discussed briefly. The components discussed in this article are introduction, theoretical framework, research method, and discussion. Need analysis has been done to know students’ needs in order to have the appropriate materials. Need analysis gives information relating with students’ need and how to do the course. Analyzing reading material will help the lecturer how effective reading class on ESP. This study used qualitative design. ESP lecturer and students of governmental science department at University of Muhammadiyah Malang are as participants. Then, interview and observation are to collect the data. ESP lecturer was interviewed and classroom observation was done to get the information relating with the material of ESP students.